Optimizing The Performance Of Bhabinkamtibmas In Enhancing Community Services In Lilirilau District, Soppeng Regency - Novianti Pratama; Herman H; Risma Niswaty; Abd. Rahman Yus; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2025)
This study aims to analyze the optimization of Bhabinkamtibmas performance in public service delivery in Lilirilau District, Soppeng Regency. The analysis is based on six key performance indicators for public officers: work results, work proficiency, job knowledge, initiative, attitude, and discipline. The research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. Data analysis includes data condensation, data display, and conclusion drawing. The findings indicate that Bhabinkamtibmas performance remains suboptimal. A gap exists between the officers' perceptions and community expectations across almost all indicators. Although administrative reporting and forum participation are being conducted, the presence of officers in the field and their impact on enhancing community security remain limited. Identified obstacles include ineffective time management, inconsistent responsiveness, low technology utilization, weak initiative and empathy, and a lack of professionally driven discipline. Performance optimization requires a systemic approach grounded in participatory, collaborative, and public-oriented principles. Recommendations include need-based local training, strengthened inter-agency coordination, utilization of information technology, development of professional attitudes, and integration of local wisdom values in service delivery. These strategies are expected to enhance the role of Bhabinkamtibmas as responsive, human-centered, and trustworthy public service agents.